Bendamustine impairs humoral but not cellular immunity to SARS-CoV-2 vaccination in rituximab-treated B-cell lymphoma–affected patients - Vanni, Anna; Salvati, Lorenzo; Mazzoni, Alessio; Lamacchia, Giulia; Capone, Manuela; Francalanci, Stefania; Kiros, Seble Tekle; Cosmi, Lorenzo; Puccini, Benedetta; Ciceri, Manuel; Sordi, Benedetta; Rossolini, Gian Maria; et al. (Frontiers in Immunology, 2023)
BACKGROUND: B cell lymphoma patients, are a fragile category of subjects, particularly exposed to infections and characterized by an impaired vaccination response due to the disease itself and, even more, to the chemotherapy regimen. For this reason, extensive knowledge of the immune response status of these subjects is of fundamental importance to obtain possible indications for a tailored immunization strategy. METHODS: We enrolled two cohorts of patients with B cell lymphoma under rituximab treatment or 3-24 months post-treatment. In all patients we evaluated both humoral and cellular immunological memory towards SARS-CoV-2, after standard vaccination and upon one booster dose. RESULTS: We observed no Spike-specific IgG production in patients (n=25) under anti-CD20 treatment, while patients (n=16) vaccinated after the completion of chemotherapy showed a higher humoral response.Evaluating SARS-CoV-2-specific T cells response, we found that patients in both cohorts had developed robust cellular immunity after vaccination. Of 21 patients (51%) that experienced a breakthrough SARS-CoV-2 infection, only 6 patients developed severe disease. Interestingly, these 6 patients had all been treated with rituximab plus bendamustine. Notably, we observed that Spike-specific IgG levels in rituximab plus bendamustine patients were absent or lower compared to patients treated with rituximab plus other chemotherapy, whereas Spike-specific T cell response was not different based on chemotherapy regiment. DISCUSSION: Our results show that in B cell lymphoma patients under rituximab therapy, anti-SARS-CoV-2 mRNA vaccination induces a weak or absent humoral response, but a consistent T-cell response. In addition, chemotherapy regimens with bendamustine further reduce patients' ability to mount a Spike-specific humoral response even after a long time period from chemotherapy discontinuation. These results provide evidence that different chemotherapeutics display different immunosuppressive properties, that could be taken in to account in the choice of the wright drug regimen for the right patient. Moreover, they question whether immunocompromised patients, particularly those treated with bendamustine, need interventions to improve vaccine-induced immune response.